A native chromatin purification system for epigenomic profiling in Caenorhabditis elegans - Ooi, Siew Loon (Oxford University Press, 2010)
High-resolution mapping of chromatin features has emerged as an important strategy for understanding gene regulation and epigenetic inheritance. We describe an in vivo tagging system coupled to chromatin purification for genome-wide epigenetic profiling in Caenorhabditis elegans. In this system, we coexpressed the Escherichia coli biotin ligase enzyme (BirA), together with the C. elegans H3.3 gene fused to BioTag, a 23-amino-acid peptide serving as a biotinylation substrate for BirA, in vivo in worms. We found that the fusion BioTag::H3.3 was efficiently biotinylated in vivo. We developed methods to isolate chromatin under different salt extraction conditions, followed by affinity purification of biotinylated chromatin with streptavidin and genome-wide profiling with microarrays. We found that embryonic chromatin is differentially extracted with increasing salt concentrations. Interestingly, chromatin that remains insoluble after washing in 600 mM salt is enriched at 5′ and 3′ ends, suggesting the presence of large protein complexes that render chromatin insoluble at transcriptional initiation and termination sites. We also found that H3.3 landscapes from these salt fractions display consistent features that correlate with gene activity: the most highly expressed genes contain the most H3.3. This versatile two-component approach has the potential of facilitating genome-wide chromatin dynamics and regulatory site identification in C. elegans.